The Effect of Age, Sex, Smoking and Co-Medication on Serum Levels of Venlafaxine and O-Desmethylvenlafaxine under Naturalistic Conditions - Unterecker, S.; Hiemke, C.; Greiner, C.; Haen, E.; Jabs, B.; Deckert, J.; Pfuhlmann, B. (Pharmacopsychiatry, 2012)
Venlafaxine (VEN) is a modern antidepressant which exerts both serotonin and norepinephrine reuptake inhibition. In this study we examined the influence of age, sex, smoking, and co-medication on serum levels of VEN and its metabolite O-desmethylvenlafaxine (ODVEN) in patients treated with VEN under naturalistic conditions.We retrospectively evaluated 478 TDM analyses of VEN requested in the Pychiatric University Hospitals of Mainz, Regensburg, and Würzburg. The determination of serum levels was performed by virtually identical chromatographic methods in the TDM laboratories of the participating hospitals.Serum levels varied widely on each dose level. Women had about 30% higher dose-corrected serum levels of VEN and ODVEN than men (p<0.01), and patients older than 60 years showed about 46% higher levels of both compounds than younger ones (p<0.01). In smokers, mean serum levels of ODVEN were 21% lower than in non-smokers. Combining these variables a considerable increase of the differences between the subgroups was found indicating an additive effect. ANOVA over the 8 different groups was significant for ODVEN (p<0.01) and sum (p<0.01), but not for VEN (n.s.). Co-medication with other psychotropic drugs was associated with a decreasing ODVEN/VEN ratio indicating a reduced metabolism in patients receiving polypharmacy.These findings show that TDM is useful to identify factors affecting the pharmacokinetic properties of VEN. It is concluded that sex, age and smoking should be considered for optimal dosing of patients with VEN.
Keywords: pharmacokinetics; venlafaxine; depression treatment